Drug Prescription Pattern Of Outpatients In A Tertiary Care Teaching Hospital In Maharashtra - BHAVESH K. LALAN,; R. S. HIRAY,; B. B. GHONGANE, (International Journal of Pharma and Bio Sciences, 2012)
A cross sectional descriptive study was conducted in Out Patient Department of Sassoon Hospital. Twelve hundred prescriptions were randomly collected over 10 days and recorded over a ‘prescribing indicator form’. The data was analyzed using WHO ‘prescribing indicators’. Average number of drugs per encounter was 3.62. Encounter with an antibiotic prescribed was 46.17%, with a FDC it was 46.67% and with an injection it was 0.17%. The most common group of drug prescribed was Vitamins and Minerals (24.44%), followed by Analgesics (17.76%), Antimicrobials (16.59%) and Antiulcer drugs (16.49%). Most common drug prescribed was Ranitidine (15.89%), followed by Vitamin B complex (11.03%) and Diclofenac (10.69%). Most common antibiotic prescribed was Ciprofloxacin (3.80%), followed by Amoxicillin (3.73%) and Metronidazole (2.30%). The prescribing practices in this study are not satisfactory. The study was undertaken to give feedback to the prescribers, so as to create awareness about the rational use of drugs.